The Parthenon Frieze - Jenkins, Ian (Univ. of Texas Press, 1994)
Most of what survives of the frieze is now in the British Museum or the Acropolis Museum in Athens; the rest is scattered among a number of European collections. This book reconstructs the frieze in its entirety according to the most up-to-date research, with a detailed scene-by-scene commentary, and the superb quality of the carving is vividly shown in a series of close-up photographs. In his introduction Ian Jenkins places the frieze in its architectural, historical and artistic setting. He discusses the various interpretations suggested by previous scholars, and finally puts forward a view of his own